Broken Student Resilience Analysis Home Class VIII Al Washliyah 63 Junior High School Leading - Aprilia Sari, Riszka; Abdurrahman, Abdurrahman; Darmayanti, Nefi (UNIVERSITAS PAKUAN, 2024)
In an educational context , broken home students often face major challenges , both emotionally and socially , which can affect their academic and personal development . Students who come from broken Home usually experience instability in family relationships , lack of emotional support , and greater mental stress compared to students from intact families . This research aiming to analyze the resilience of broken home students in class VIII at Madrasah Tsanawiyah Al Washliyah 63 Punggulan . Resilience is an individual's abilities to rise and adapt to the face of various pressure or trauma. Students from broken Home often face greater emotional challenges , such as a lack of support from family and an unstable environment . This research uses descriptive qualitative methods to understand the factors that shape student resilience , including the roles of family , friends and teachers . The research results show that social support , coping skills , and optimism play an important role in forming students ' psychology resilience . The conclusion of this research emphasizes the need for more intensive support from the school and the environment to help broken home students develop strong resilience .